Preparatory studies for modelling production on protected grasslands - Antal, Zsuzsanna; Huzsvai, László (Acta Agraria Debreceniensis, 2007)
There is a mutual dependence between nature conservation activity and agriculture in Hungary, as the management of the protected areas cannot be achieved without ecological farming methods. Moreover, viable economic activity can be only imagined through the harmonization of agricultural and nature conservation interests. From a nature conservation point of view, grass management systems play the greatest role in domestic agricultural systems. Yet, due to the prohibition of certain management methods and the spatial and temporal restraints on grazing, nature conservation activities have priority on protected grasslands. While nature conservation activity is still of prominent importance, it is not equally suitable for the economical management of protected grasslands per se. With our examinations, we would like to emphasize the common interests of these mutually dependent activities and to promote bilateral cooperation. Our aim is to model the production of grass on the great pastureland of Hajdúbagos. Potential grass production levels are easily calculable with a computer model based on data collected through a series of test harvests, as well as by factoring in changing climatic factors and by simulating the effects of grazing animal species and stocks. This model is not only useful for determining the optimal number of the grazing animal stock and grazing method, and therefore the most suitable management strategy, but it also supports local farmers to be able to plan their activities. In this way, both nature conservation and economic aims can be easily harmonized, which would be an important factor for the sustainable development of rural areas.